Effects of anaerobic exercise training on human function based on multiple linear regression - Xiao, Haiting; Peng, Kun; Sun, Liman; Pan, Feng (Frontiers in Physics, 2023)
In recent years, with the continuous enhancement of people's fitness awareness, increasingly people are engaged in anaerobic exercise training. For ordinary people, anaerobic exercise training can significantly improve their physical fitness and immunity, reduce the risk of disease, to improve the quality of life. For athletes, proper anaerobic exercise training is the guarantee for their high-quality results. Although anaerobic exercise training can improve physical fitness, due to the lack of necessary exercise training guidance, people also have some problems in anaerobic exercise training. For example, unreasonable exercise methods and excessive exercise can cause physical damage. Moreover, the training concept of the traditional training mode is relatively backward, and the guiding effect of anaerobic exercise training practice is not obvious. Therefore, in order to give full play to the role of anaerobic exercise training and enhance human function, this paper studied the effects of anaerobic exercise training and anaerobic exercise training on human function based on multiple linear regression analysis (MLR). An anaerobic exercise training model based on MLR was proposed, and research experiments were carried out from seven aspects, such as exercise ability, immunity, and cardiovascular function. The experimental results showed that the anaerobic exercise training mode based on MLR can improve exercise capacity by 5.48%, immunity by 3.08%, and cardiovascular function by 4.31%.